KENT(Lİ)LEŞME PRATİĞİNDE YENİ BİR OLGU: TAZİYE EVLERİ ve FARKLILAŞAN sosyo-kültürel PRATİKLER - (:unkn) unknown (My University, 2012)
Bütün dünyada olduğu gibi Türkiye 'de de kentleşme süreciyle birlikte toplumsal yaşamın birçok alanında yapısal farklılaşmalar gerçekleşmektedir. Modernleşmenin belirgin bir yüzünü temsil eden kentleşme dinamiği, kırsal yaşamın aurasında şekillenen yaşam pratiklerini kendine özgü normlar çerçevesinde yeniden biçimlendirmektedir. Kente taş(ın)an nüfus, kentin normatif düzeni içinde ekonomik, siyasal, toplumsal, kültürel ve dinsel alanlarda kente tutunma anlamında farklı stratejiler geliştirmeye çalışmaktadır. Bu bağlamda ekonomik yaşam, siyasal tercih, sosyalleşme biçimi, kadın-erkek ilişkileri, aidiyetler, dinsel tutum ve pratikler gibi birçok alanda belirgin bir biçimde yeni tarzlar oluşmaktadır. Bu çalışmanın amacı, Doğu ve Güneydoğu Anadolu bölgelerinde geleneksel yaşam kalıpları içinde yerleşik bir karakter kazanmış bir sosyo-dinsel ritüelde, taziye geleneğinde, kentleşme süreciyle birlikte gerçekleşen aşınmaları ve yine kentleşme mantığının bir sonucu olarak ortaya çıkan "taziye evleri" oluşumunu sosyolojik açıdan analiz etmektir.

As in the whole world, structural differentiation is taking place in a lot of realms of social life in Turkey too, together with the urbanisation process. Urbanisation dynamics, which represents an apparent face of modernisation, is reshaping living practices shaped within the aura of rural life, in the framework of unique norms. The population moving (in other words, overflowing) to the city is trying to develop different strategies in economic, political, cultural and religious areas within the normative order of the city, to survive in the city. In this context, new styles are markedly emerging in many areas such as economic life, political choice, socialisation pattern, intersexual relations, belongings, religious attitude and practices. In this respect, the purpose of this study is to analyse, from a sociological perspective, the erosion in a religious ritual, the tradition of condolence, which has earned a fundamental character in the traditional living patterns in the Eastern and Southeastern Anatolian Region, brought about by the urbanisation process, and the Condolence Houses which again emerge as a consequence of the urbanisation dialectics.
A new fact in the urbanisation practice: Condolence houses and differentiating socio-cultural practices